2009
DOI: 10.1182/blood-2008-07-166942
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase regulates the rate of endothelial progenitor cell differentiation

Abstract: Circulating endothelial progenitor cells (EPCs) are incorporated into foci of neovascularization where they undergo differentiation to mature endothelial cells (ECs). We show here that the enzyme sphingosine kinase-1 (SK-1) regulates the rate and direction of EPC differentiation without effect on the hematopoietic compartment. EPCs have high levels of SK-1 activity, which diminishes with differentiation and is, at least partially, responsible for maintaining their EPC phenotype.EPCs from SK-1 knockout mice for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 65 publications
5
62
0
Order By: Relevance
“…Cells were infected with a dose of virus previously determined to lead to a five-to tenfold increase in SK-1 activity and the same dose of control EV adenovirus was used. 17 …”
Section: Inhibition Studies Using Human Sk-1 Adenovirus Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were infected with a dose of virus previously determined to lead to a five-to tenfold increase in SK-1 activity and the same dose of control EV adenovirus was used. 17 …”
Section: Inhibition Studies Using Human Sk-1 Adenovirus Transductionmentioning
confidence: 99%
“…However, S1P can also act intracellularly, possibly through histone deacetylases 16 or other as yet unknown binding partners, where the ablation of receptor signaling through both chemical or genetic mechanisms does not abrogate S1P effects on cell proliferation, Ca 2ϩ mobilization, EC survival, nor the differentiation of endothelial progenitor cells. 10,17 SK-1 has two functional states, an intrinsic or basal state and an agonist-induced activated state, which requires its phosphorylation and is responsible for its oncogenic properties. 18 More recently we observed that SK-1 activates ␣ v ␤ 3 integrin to mediate EC survival signaling pathway via formation of a heterotrimeric complex between SK-1, ␣ v ␤ 3 and CD31.…”
mentioning
confidence: 99%
“…HUVEC were seeded on angiogenesis plate (1 μ-Slide Angiogenesis ibiTreat; Ibidi, Munich, Germany) coated with 12 μl of Matrigel (354234, BD Biosciences, Bedford, MA, USA). The number of tubes was counted as previously described [22,27] and data were derived from an average of four donors.…”
mentioning
confidence: 99%
“…44 Increasing evidence for S1P as a bone fide second messenger 11 includes our own studies showing that S1P receptor inhibitors VPC23019 and JTE-013, although efficient for inhibiting agonist-induced SK-1 activity, 24,45 failed to have any effect on survival in the SK-1-overexpressing EC 24 or on the differentiation of endothelial progenitor cells. 46 Paik et al 47 previously described S1P 1 -and S1P 3 -mediated Rho signaling in ␣ v ␤ 3 activation for EC migration. This current study suggests a mode of action via membrane-localized components that is key to survival signaling pathways.…”
Section: Discussionmentioning
confidence: 99%